2018
DOI: 10.3390/app8030409
|View full text |Cite
|
Sign up to set email alerts
|

Depth Retrieval Procedures in Pulsed Thermography: Remarks in Time and Frequency Domain Analyses

Abstract: Featured Application: The present study intends to show the potentiality of pulsed thermographic imaging to quantitatively characterise hidden defects in Carbon Fibre Reinforced Polymers. By comparing the performance of different depth retrieval procedures, it was possible to evaluate the produced depth estimation accuracy and to define the impact of different experimental and analysis parameters in quantitative analysis. Abstract:In the present study, a Carbon Fibre Reinforced Polymer (CFRP) sample of trapezo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…However, the selection of such a reference pixel is often non-trivial since it requires a priori information about the sample and its defects. As a practical alternative, the average phase value of the entire sample can also be used as reference value [28]. In this paper, the phase contrast is calculated according to the latter manner.…”
Section: Background Of Pulsed Phase Thermography (Ppt)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the selection of such a reference pixel is often non-trivial since it requires a priori information about the sample and its defects. As a practical alternative, the average phase value of the entire sample can also be used as reference value [28]. In this paper, the phase contrast is calculated according to the latter manner.…”
Section: Background Of Pulsed Phase Thermography (Ppt)mentioning
confidence: 99%
“…On the other hand, in the field of ultrasonic NDT, the drop technique is a standard technique for defect size estimation, in which a defect is sized by applying a cut-off at a specific percentage of the defect's maximum amplitude [25][26][27]. For FT, several procedures for defect depth estimation have been introduced [21,[28][29][30][31][32][33][34], most of which rely on the idealized 1D solution for the heat diffusion equation or on artificial neural networks. With respect to PPT, it is known that there does not exist an unambiguous relationship between the phase angle and the defect depth [30], which means that individual phase (contrast) images cannot be used for proper depth inversion.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the present approach focuses on a systematic search of the maximum phase contrast and its corresponding frequency, analogous to DTT. The phase contrast was calculated by either subtracting the phase profile of a single known sound pixel, the mean phase value of a known sound area, or the mean phase value of the entire inspected sample, from the phase profile of every pixel [36]. In this study, the phase contrast was calculated by the latter approach.…”
Section: Single-bin Evaluation: Frequency-domain Tomography (Fdt)mentioning
confidence: 99%
“…The results showed that the two different analyses provided efficient depth estimations, with frequency domain analysis demonstrating greater accuracy. Finally, predicting errors were observed in both cases and the factors responsible for these errors were defined and discussed [23].…”
Section: Overview Of the Accepted Papersmentioning
confidence: 99%